A144 AN EXPLORATORY PROSPECTIVE LONGITUDINAL STUDY INTO THE BREASTFEEDING PRACTICES OF WOMEN WITH INFLAMMATORY BOWEL DISEASE. (1st March 2018) - Nguyen, V V; Baker, C; Andrishak, S R; Ambrosio, L; Berga, K; Dieleman, L A; Halloran, B P; Kroeker, K I; Peerani, F; Wong, K; Fedorak, R; Huang, V
Abstract: Background: Breastfeeding is important for infant health, with recommendations to exclusively breastfeed until 6 months postpartum. Women with inflammatory bowel disease (IBD) have been reported in retrospective and survey studies to avoid initiating or cease breastfeeding early, with rates that differ between countries, and decades. Aims: We aimed to explore breastfeeding practices among a cohort of women with IBD and healthy volunteer mothers through a prospective longitudinal survey study. Methods: Adult women with and without IBD were invited to complete surveys regarding breastfeeding status at delivery, postpartum 3, 6, 9, and 12 months. Sociodemographic data on education and income level were obtained. Women with IBD were assessed for clinical disease activity using the Harvey Bradshaw Index for Crohn's disease (CD) or partial Mayo score for ulcerative colitis (UC). Rates of breastfeeding were calculated at each time point and compared between maternal groups. Results: A total of 80 IBD (25 CD and 43 UC) mothers and 12 healthy mothers completed surveys. Similar proportions of IBD mothers and healthy mothers initiated breastfeeding (95.6% vs 100.0%, p=0.458) and continued until 3 months postpartum (75.0% vs 91.7%, p=0.202). Fewer IBD mothers breastfed at 6 months compared to healthy mothers (54.4% vs 90.9%, p=0.023). There was no significant difference in breastfeeding based on delivery method, or IBD disease activity (for IBD mothers). Lower income mothers were less likely to breastfeed than those with higher income brackets.The main reasons reported for cessation of breastfeeding were insufficient milk production, initiation of new medications, and baby was sick/unwilling to breastfeed. Conclusions: Breastfeeding practices differ among mothers with IBD and healthy mothers, with a large proportion of IBD mothers ceasing to breastfeed earlier than the recommended 6 months postpartum. Future research into these reasons may contribute towards a better understanding of the complex interaction between maternal IBD and milk production, IBD medications and breast milk composition, and impact of maternal IBD and breast feeding on infant health. Funding Agencies: CEGIIR University of Alberta